Pengaruh Ukuran Perusahaan Terhadap Manajemen Laba Dengan Tax Avoidance Sebagai Variabel Mediasi: Studi Kasus Perusahaan F&B Yang Terdaftar di Bei Pada Tahun 2022-2024 - Arimanda, Dhea Vanesa; Kusumawardani, Anisa (Multidisciplinary Journal of Education , Economic and Culture, 2026)
This study aims to examine the effect of firm size on earnings management with tax avoidance as a mediating variable in food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The research is motivated by inconsistent findings in prior studies and the limited focus on the F&B sector. This study employs a quantitative approach with a causal associative design. The sample was selected using purposive sampling, resulting in 29 companies with 87 observations. Secondary data were obtained from annual reports, and the analysis was conducted using Partial Least Squares (PLS) to assess both direct and indirect relationships among variables.. The results indicate that earnings management has a negative and significant effect on firm size. Meanwhile, tax avoidance does not have a significant effect on either earnings management or firm size, and it does not mediate the relationship between the two variables. The low R-square value suggests that the model has limited explanatory power.